"George and I just went on a fabulous cruise. We saw orca whales, seals, eagles, soaring cliffs, peaceful inlets." "Wow! What did that cost?" "About 15 bucks." - Raeside, Adrian (Victoria Times Colonist, 1998)
"George and I just went on a fabulous cruise. We saw orca whales, seals, eagles, soaring cliffs, peaceful inlets." "Wow! What did that cost?" "About 15 bucks."